(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT: Human capital development and health and well-being are known to be significantly impacted by nutrition. Africa’s nutritional status has deteriorated remarkably over the past decade, increasing questions regarding the region’s capacity to achieve the sustainable development goal SDG 2 that focuses on nutrition and food security. One of the highest rates of malnutrition is found in West Africa. Therefore, dietary deficiencies are frequently caused by a lack of funds, resources, such as labor and land, and time, particularly for women. Strengthening West African Women through Nutrition concepts is described in this paper. Strengthening or empowering women changes dietary patterns in the household, improves nutrition, and thus impacts diet-related health outcomes in Africa. We discovered causal relationships between certain areas of food security and dietary enhancement and women’s empowerment. It has been demonstrated that empowering women through nutrition decision-making improves household nutrition rates overall.